PERANCANGAN LOGO DAN MEDIA PROMOSI SOFTWARE RITELAA BERBASIS POP ART SEBAGAI UPAYA MENCIPTAKAN BRAND AWARENESS - Hadiani, Ulfi; Budiardjo, Hardman; Khoiriqqoh, Abdullah (Jurnal Art Nouveau, 2016)
AbstractLogo and Media Campaign on the identity of a product is to make these products are able to compete and easily recognizable in the minds of the public / consumers. In East Java alone so many companies that need a logo and promotional media to be known well in the minds of consumers. Media promotion of adequate capable of making a product has a high value. Taking one CV in Surabaya, CV. Dapurmedia to do branding logo creation and promotion of media-based software Ritelaa pop art as an effort to create brand awareness. Problems in this final project is how to design a logo and promotional media on the Ritelaa products to create brand awareness in the minds of consumers in order to be known. Logo designed a simple design style pop art that aims to be easily recognized and remembered in the minds of the people and brought the color and characteristics of simple shapes. The research method uses qualitative methods with data collection technique using observation, interviews, literature, and FGD. The concept used in the design is the "modern" sharp and straight. Lead to the design are clear in terms of design firm, clear, and precise. The concept will be applied to any design that include logos and other penndukung media. Results from logo creation and media campaign against Ritelaa software is an attempt menggembangkan CV. Dapurmedia to have high competitiveness in terms of logo / brand. designed logo is a form of identity CV product. Dapurmedia namely Ritelaa people to easily recognize and remember the product.Â Keywords: Design, Logo, Media Unit Promotion of Small and Medium Pop Art, Brand Awareness, Ritelaa, modern.